APLIKASI TEKNOLOGI PUPUK ORGANIK DAN TEKNIK PEMANGKASAN UNTUK MENINGKATKAN PRODUKSI JAGUNG HIBRIDA DI KECAMATAN GALESONG KABUPATEN TAKALAR - Netty, Netty; Karman, Nurliani; Boceng, Annas (Jurnal BALIRESO, 2016)
Takalar an area of maize development in South Sulawesi. One of the District in Takalar is Galesong which has Gapoktan (unity of farmer groups) which consists of 28 farmer groups. Most farmers cultivate hybrid corn to meet the demand for raw materials for poultry feed. Production of farmers in this region is still low at an average of 3.94 tons per hectare is far below the potential of hybrid maize production is 10.0-13.0 tons per hectare. The low productivity of maize is caused by cultivation techniques are not optimal for examples fertilization rely on inorganic fertilizer alone, lack irrigation water, which is not a optimal spacing, pests and diseases. Corn hybrids require large amounts of nutrients to achieve high production. However, the use of inorganic fertilizers, such as urea continuously for a long time on the ground can adversely affect the quality of the soil. The purpose of this program is to provide guidance to the partners in the group of farmers increase production of hybrid corn, reducing the use of inorganic fertilizers and the use of crop residues as organic fertilizer. The method applied in this program is to provide training and demonstration plots to farmers groups partners. Determination of farmer groups using purposive sampling method, the Romang Romang Sapiria Sapiria 1 and 2 as well as Paraikatte with three basic considerations of hybrid maize farming in the dry season. Each selected farmer groups 5 farmers to be trained. Before and after training are given a pre-test and post-test. Results of demonstration plots activities using organic fertilizers made farmers group partners can increase the production of hybrid corn is 10.8 tons per hectare. These results differ significantly from the average yield of farmers using inorganic fertilizers is 7.6 tons per hectare.